4 - Le squelette fragile du pouvoir colonial : travail forcé et réseau routier en Basse- Casamance dans l’entre-deux-guerres - Romain Tiquet, (Afrika Zamani, 2022)
This article analyzes the local implementation of a form of forced labour in Senegal during the inter-war period: the construction of the road network. Building on the example of the construction of the Tobor–Ziguinchor road in Casamance by forced labourers, the objective of this article is to show how local contingencies have influenced the progress of construction works, making territory or federation-wide rules inapplicable locally. Thus, to discuss the forced labourers’ forms of mobilization makes it possible to reflect on a new geography of work that runs contrary to the “Dakar-centric” tendency of classical historiography, which all too often views the Senegalese territory as a fictional whole. Moreover, people subjected to forced labour on road construction sites were far from passive actors in a system. They reacted in multi-faceted manners, succeeding in defeating an intrinsically arbitrary system.